2020
DOI: 10.3390/electronics9101659
|View full text |Cite
|
Sign up to set email alerts
|

HyperLedger Fabric-Based Proactive Defense against Inside Attackers in the WSN With Trust Mechanism

Abstract: In Wireless Sensor Networks (WSNs), the Trust Mechanism (TM) is used to defend against insider attacks by measuring the trustworthiness of all inside sensor nodes in the network. Thus, each sensor node with TM observes its neighbor nodes’ behaviors, evaluates their trustworthiness as numeric trust values, and captures untrustworthy nodes as inside attackers. Although the defense performance of trust mechanisms can be further improved by sharing the information about inside attackers detected by TM with all sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The scheme in [30] The scheme in [31] The scheme in [29] MSTW The scheme in [30] The scheme in [31] The scheme in [29] MSTW Figure 7: The coverage of different schemes in [29][30][31]. 10 Wireless Communications and Mobile Computing…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scheme in [30] The scheme in [31] The scheme in [29] MSTW The scheme in [30] The scheme in [31] The scheme in [29] MSTW Figure 7: The coverage of different schemes in [29][30][31]. 10 Wireless Communications and Mobile Computing…”
Section: Discussionmentioning
confidence: 99%
“…The trustworthiness is an emerging security technology based on network dynamic parameters, which can estimate the level of network security in HWSNs. The problems of node integrity and authentication are addressed utilizing the trustworthiness in [7][8][9][10]. The investigations and studies have shown that the recommended trust and the dynamic network information of the current node can effectively evaluate the node security level.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (1) demonstrates how WSN can be utilized for detecting intrusions. Sensor nodes (SN), cluster heads (CH), and sink nodes (sink) are all types of nodes in a such network [29,30]. To reduce communication burden and energy consumption, this network employs distributed intrusion detection.…”
Section: Wsn Intrusion Detection Architecturementioning
confidence: 99%
“…The so-called insider packet drop attacks refer to a set of attacks where compromised nodes intentionally drop packets [1,2]. These attacks have become a serious security threat in WSNs [1,[3][4][5][6][7]. A well-positioned attacker can be on the routing path of many nodes and thus receive many data packets.…”
Section: Introductionmentioning
confidence: 99%